Design for climate change - Gething, Bill; Puckett, Katie (London : RIBA Publishing, 2013)
Climate change is a pressing concern for the construction sector. Building designers are already on the front line of reducing global greenhouse gas emissions in order to avoid catastrophic climate change, meeting increasingly tough standards and regulations on new developments and refurbishments. Now they must rise to a parallel challenge: helping society adapt to a climate that is already changing, and which will to continue to change for many years to come. Our built environment, and the way buildings are designed, constructed and managed, has evolved in response to a climate that has been broadly consistent for hundreds of years. That climate is changing at an unprecedented rate and, within a generation, our buildings may have to cope under very different conditions. How will today's buildings perform in hotter summers and with more frequent storms, floods and droughts? How can designs be future-proofed and existing buildings preserved, and at what cost?
Includes bibliographical references and index.
Keywords: Architecture and climate; Buildings -- Energy conservation; Buildings -- Heating -- Control; Buildings -- Cooling -- Control